Pencarian Clique Maksimal dan Bilangan Clique pada Graf Sederhana Menggunakan Modifikasi Algoritma Clique - Shintia Pratiwi; Armiati Armiati; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2018)
Abstract – Finding maximal clique is a problem to get a clique with the maximum number of points on a graph, where the selected points are the points that are connected to each other. Finding maximal clique in a graph would be easier if using an algorithm. One of algorithms that can be used to determine the maximal clique is clique algorithm. However, the clique algorithm still has a weakness that the process is a relatively long process because it has two procedures. Therefore, in this study a modification to this algorithm. An algorithm not only must be correct, but also must be efficient. The efficiency of an algorithm is measured from the execution time of the algorithm and the space of memory that is required to run it. After modification is done to clique algoritma, the time of complexity asymptotic algorithm gained is .